T and B Cell Composition and Cytokine Producing Capacity Before and After Bariatric Surgery - Wijngaarden, L. H.; Taselaar, A. E.; Nuijten, F.; Harst, E. van der; Klaassen, R. A.; Kuijper, T. M.; Jongbloed, F.; Ambagtsheer, G.; Klepper, M.; IJzermans, J. N. M.; de Bruin, R. W. F.; Litjens, N. H. R. (Frontiers in Immunology, 2022)
Morbid obesity is associated with a chronic state of low-grade inflammation, which may lead to accelerated differentiation of T and B cells. These differentiated immune cells are strongly cytotoxic and have an increased pro-inflammatory cytokine producing capacity. Furthermore, the anti-inflammatory function of the T and B cells decreases. The aim of this study was to evaluate the effect of morbid obesity on the subset profile and cytokine producing capacity of T and B cells. Subsequently, we assessed whether bariatric surgery affected the subset profile and cytokine producing capacity of these cells. We determined the proportion of T and B cell subsets and their cytokine producing capacity in peripheral blood collected from 23 morbidly obese patients before and three months after bariatric surgery using flow-cytometry. We compared this with the results of 25 lean controls. Both CD4+ and CD8+ T cells showed a more differentiated subset profile in morbidly obese patients as compared to lean controls, which was not recovered three months after bariatric surgery. The B cell composition of morbidly obese patients after bariatric surgery adjusted towards the profile of lean controls. However, the IL-2 and IFN-γ producing capacity of CD8+ T cells and the IL-2, IFN-γ, TNF-α and IL-10 producing capacity of B cells was not restored three months after bariatric surgery. In conclusion, the data suggest that the immune system has the capacity to recover from the detrimental effects of morbid obesity within three months after bariatric surgery in terms of cell composition; however, this was not seen in terms of cytokine producing capacity. The full restoration of the immune system after bariatric surgery may thus take longer.